2018
DOI: 10.1016/j.scitotenv.2017.09.164
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved fulvic acids from a high arsenic aquifer shuttle electrons to enhance microbial iron reduction

Abstract: It was demonstrated more than two decades ago that microorganisms use humic substances, including fulvic acid (FA), as electron shuttles during iron (Fe) reduction in anaerobic soils and sediments. The relevance of this mechanism for the acceleration of Fe(III) reduction in arsenic-laden groundwater environments is gaining wider attention. Here we provide new evidence that dissolved FAs isolated from sediment-influenced surface water and groundwater in the Bengal Basin were capable of electron shuttling betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Raw water is sustained for two hours in inlet compartment simultaneously exposing to air (oxygen). Therefore As (III) and Fe (II) are oxidized to As (V) and Fe (III) respectively (Ilgen et al, 2017;Kulkarni et al, 2018;Meng et al, 2017). Redox process of As þ3 , Fe þ2 to As þ5 , and Fe þ3 is expected to be completed in two hours (Leupin and Hug, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Raw water is sustained for two hours in inlet compartment simultaneously exposing to air (oxygen). Therefore As (III) and Fe (II) are oxidized to As (V) and Fe (III) respectively (Ilgen et al, 2017;Kulkarni et al, 2018;Meng et al, 2017). Redox process of As þ3 , Fe þ2 to As þ5 , and Fe þ3 is expected to be completed in two hours (Leupin and Hug, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…HAs were extracted from hardwood bark compost (Sanyo-Bark, Sanyo-Chip Industry, Japan), softwood bark compost (Daishizen, Green-Sogyo Co., Ltd., Japan) and peat powder in Aberdeen shire (River-Import, Japan), and then purified according to IHSS procedures. 18,19) Yields of HAs were evaluated by dividing the HA (g, dw) obtained in a one-time extraction by an amount of initial material taken compost or soil (kg, dw). 1 000 mg L − 1 stock solutions of HAs were prepared by dissolving freeze dried HA powder in 0.04 M aqueous NaOH.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…[13][14][15] Attention has focused on the electron shuttle effect of humic substances which could accelerate the metal reductive reaction in sediments or aquatic environments. [16][17][18] Labile organic substances, such as saccharides, could also contribute to the production of electrons by becoming a microbial energy source. 18) A structural analysis of humic acid (HA) indicated that anaerobic bacteria are activated in the presence of a fertilizer composed of steelmaking slag and compost during a 6-month period of incubation in coastal seawater.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,7,[11][12][13] While sedimentary DOM from peat layers, 9,[14][15][16] as well as surfacederived organic carbon, [17][18][19] have been suggested, the source of labile DOM is still a matter of much debate. 20,21 Beyond labile DOM, recent studies also highlight the potential influence of humic and fulvic acids (refractory organic polymers) in As mobilization through electron shuttling, [22][23][24][25] or competition for sorption, 26 and complexation processes. 27,28 Since the chemical composition of DOM defines its reactivity in the environment, 29,30 the ability to track the different chemical fractions of DOM is essential to better understand its role on arsenic mobilization in groundwater.…”
Section: Introductionmentioning
confidence: 99%